2022
DOI: 10.3390/plants11212969
|View full text |Cite
|
Sign up to set email alerts
|

Liposomal Formulation of Botanical Extracts may Enhance Yield Triggering PR Genes and Phenylpropanoid Pathway in Barley (Hordeum vulgare)

Abstract: This work aimed to study the plant conditioning effect and mode of action of a plant-based biostimulant used in organic farming. This new generation plant biostimulant, named ELICE16INDURES®, is rich in plant bio-active ingredients containing eleven supercritical botanical extracts encapsulated in nano-scale liposomes. The dose–response (10 to 240 g ha−1) relationship was tested in a field population of autumn barley (Hordeum vulgare) test crop, and underlying molecular mechanisms were studied. Applying nanote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 80 publications
0
9
0
Order By: Relevance
“…This officially licensed product was developed based on an innovative green technology that improves plant vitality and resilience by stimulating their immune system (for its biologically active ingredients, see TableS 1 ). The advantage of this product is the recommended ultra-low volume (ULV) drone spraying application (20–60 g/ha, based on the authorization document) which increases the uniform spray pattern providing better homogeneity for the plants which leads to increases in yield levels [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…This officially licensed product was developed based on an innovative green technology that improves plant vitality and resilience by stimulating their immune system (for its biologically active ingredients, see TableS 1 ). The advantage of this product is the recommended ultra-low volume (ULV) drone spraying application (20–60 g/ha, based on the authorization document) which increases the uniform spray pattern providing better homogeneity for the plants which leads to increases in yield levels [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…We tested the ‘Garlic lipo’ agent as an active component of ELICE Vakcina ® , a member of the Elice16 product line developed in the Research Institute for Medicinal Plants and Herbs (RIMPH) Ltd., Hungary ( accessed on 1 January 2023), and which formulation and biological effect have already been characterized [ 36 , 38 ]. According to the formulation technology of ELICE Vakcina, the supercritical fluid extraction of fine-grated fresh garlic with natural carbon dioxide (FLAVEX Naturextrakte GmbH, Rehlingen-Siersburg, Germany) was encapsulated in sunflower lecithin-based liposomes.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, airborne nanoparticles disintegrated into safe molecular building blocks (phospholipids) over longer airborne distances to reduce the environmental toll. An example is the liposome-encapsulated plant conditioner product, Elice16indures ® of RIMPH Ltd., Budakalász, Hungary (containing 11 herbal CO 2 extracts involving garlic), and in both phytotron and earlier field experiments, it was found that this agent triggered the plant defense system through hormonal pathways in Hordeum vulgare [ 36 ] and Glycine max [ 37 , 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…They found that bacterized seedlings showed a slight improvement in wheat roots and shoots, and the polyphenol oxidase was greater in the roots and shoots. Hegedus et al [40] reported that the overexpression of glucan endo-1,3-beta-glucosidase has been linked to a variety of physiological and developmental processes, as well as resistance to biotic and abiotic stress. This suggests that these genes may play an important role in plant resistance to various stresses and diseases.…”
Section: Machine Learningmentioning
confidence: 99%